Potential application derived from the essential oil of pandan leaves (Pandanus Amaryllifolis Roxb.) - Swee Leong, Lee (2012)
Pandan(Pandanus Amaryllifolius Roxb.)is an erect green plant with the woody aerial roots and fan-shaped sprays of long, narrow, blade-like leaves leaf.It is widely used as natural flavoring in South East Asian dishes.Pandan leaves are also used by many people as an odour repellent in their cars due to its nature as an insect repellent and its aromatic fragrance.The major compound contributing to its aromatic fragrance is 2-acetyl-1-pyrroline (2AP).The potential usage of the essential oil as a natural air freshener was studied. The effects of the extraction temperature and period on quantity and quality of extraction yield were also studied. Experimental parameters included the temperature and extraction period.In this study, essential oil was extracted from pandan leaves by using the Microwave Assisted-solvent Extraction method, followed removal of ethanol solvent by using Rotary Evaporator.The chemical compounds inside extract included 2AP were identified by Fourier Transform Infrared Spectroscopy (FTIR),while the concentration of 2AP was analyzed by Gas Chromatography-Flame Ionization Detector (GC-FID). The concentration of 2AP for each parameter was determined by comparing the internal standard graph of trimehylpyridine (TMP) using GC-FID.The results shown that yield, volume of extracted essential and concentration of 2AP in essential oil increased with the extraction temperature before reaches the optimum point.Then,they decreased for higher temperature for extraction process due to decomposition of 2AP.On the other hand,the yield,volume of extracted essential oil and concentration of 2AP in essential oil decreased with increment of extraction period and then almost constant for longer period. This is because further exposure in high temperature for long period decomposed the heat sensitive compounds inside essential oil.Therefore, the extraction process at temperature 88oC and 30 minutes produced the highest yield of extract and concentration of 2AP respectively.After the optimum condition of extraction method was determined,high amount of pandan leaves extract was produced for further research. Beaker A with 25 ml sample and beaker B with 25 ml water was given to 6 rooms in Kolej Kediaman 4 for sensory evaluation. The 6 rooms were chosen random, but have almost same environment condition.There are 5 people in each room to evaluate 5 criteria which are correctness,persistence, smell,intensity and overall acceptance for one week.They also measured the volume of water and sample left in beaker in every single day.Based on the result,most panels gave high rating grade for persistence, correctness and smell. However, they gave low rating grade for overall acceptance and intensity due to low concentration of 2AP in essential oil.The recommendation is to increase the concentration of 2AP inside essential oil in order to have high performance. The essential oil of pandan leaves has high potential to be a natural air freshener in daily life.